2011
DOI: 10.1111/j.2042-7158.2011.01323.x
|View full text |Cite
|
Sign up to set email alerts
|

Light effect on the stability of β-lapachone in solution: pathways and kinetics of degradation

Abstract: This study provides useful information for the development of βLAP dosage forms, their storage, manipulation and quality control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 21 publications
(22 reference statements)
3
9
0
Order By: Relevance
“…HPLC chromatograms of the βLAP samples stored in the dark did not show modifications after 1 month and 3 months (profiles not shown). However, after storage for 6 months, the significant reduction of the βLAP peak combined with the appearance of an extra small peak, characteristic of hydroxylapachol, indicated that hydrolytic degradation of the drug had occurred, as previously described for degradation of βLAP in solution . Chromatograms of samples exposed to the light showed changes after a 3‐month period that can be related to the main photodegradation products, phthalic acid and the 6‐hydroxy‐3methylene‐3H‐isobenzofuran‐1‐one, which is in agreement with our previous results …”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…HPLC chromatograms of the βLAP samples stored in the dark did not show modifications after 1 month and 3 months (profiles not shown). However, after storage for 6 months, the significant reduction of the βLAP peak combined with the appearance of an extra small peak, characteristic of hydroxylapachol, indicated that hydrolytic degradation of the drug had occurred, as previously described for degradation of βLAP in solution . Chromatograms of samples exposed to the light showed changes after a 3‐month period that can be related to the main photodegradation products, phthalic acid and the 6‐hydroxy‐3methylene‐3H‐isobenzofuran‐1‐one, which is in agreement with our previous results …”
Section: Resultssupporting
confidence: 91%
“…An additional problem for βLAP formulation development is its instability. We have previously investigated the degradation mechanisms of βLAP in aqueous solution under both light conditions and in darkness, and identified the main degradation products . Light greatly accelerated drug degradation in aqueous medium, giving different degradation products depending on storage conditions .…”
Section: Introductionmentioning
confidence: 99%
“…No crystalline growth was observed under optical microscopy. Samples show that the same UV-visible spectra and β LAP amount before and after autoclaving are not significantly different [32]. Therefore, autoclaving could be recommended as a sterilization method for these intratumoral formulations.…”
Section: Resultsmentioning
confidence: 99%
“…Chromatographic detection was set at 253 nm with a photodiode array detector. The mobile phase and samples were filtered using a 0.45 μm nylon membrane (Waters, Milford, MA) 14 .…”
Section: Drug Contentmentioning
confidence: 99%